Valérius growth trajectory : a case study on competitive advantage in the portuguese textile and clothing industry - Almeida, Inês Maria Simões de (2018)
This dissertation, written in a form of case study, aims to address how a firm operating in the Portuguese textile and clothing industry was able to survive the challenges posed by the dynamics felt in the industry. It serves as a teaching instrument since it provides tools for the study of a real-life situation and application of theoretical frameworks learned in class. Valérius is a Portuguese company operating in the textile and clothing industry dedicated to the production of knitwear garments for the high premium segment, being able to craft a growth trajectory over the last years. Why is Valérius able to survive while many other companies are failing? What is on the basis of its competitive advantage? The options the company made, when facing difficult decisions in order to cope with changes on the external environment, creates a set of interesting issues to address in strategy courses, to further deepen students’ knowledge on theoretical concepts. The proposed case study delivers the base for a critical analysis of the company in order to understand where lies its competitive advantage, particularly with the study of the dynamic capabilities approach.